EffectS of ZnO nanoparticles and graphene oxide on properties of acrylic polymer nanocomposite coating - Hung, Dao Phi; Thanh, Trinh Van; Hiep, Nguyen Anh; Vuong, Nguyen Thien; Phuc, Mac Van; My Linh, Dang Thi (Vietnam Journal of Science and Technology, 2021)
Effect of ZnO nanoparticles on nanocomposite coatings based on R4152 and graphene oxide (GO) was studied.In presence of 2%wt. ZnO nanoparticle, abrasion resistance of coating increased by nearly 25% (from 75 to 92.9 L/mil) and temperature decomposition raised by 18oC. SEM images showed that nano ZnO can disperse homogenously in polymer matrix in presence of GO. Hence, photocatalytic activity of R4152/GO/ZnO nanocomposite coating was higher than that of R4152/ZnO nanocomposite coating. After 14 hours UV exposure, R4152/GO/ZnO nanocomposite coating can degrade over 80% methylene blue coated on its surface while 60% methylene blue was degraded by R4152/ZnO coatings.